Asesmen Formatif Dan Penguatan Pembelajaran Diferensiasi: Kajian Konseptual Dalam Kurikulum Merdeka - Anggi Johari Sitanggang; Ajeng Novita Aprilia; Gilbert Phineas Philetas Siahaan; Jesika Febrianty Manalu; Nada Azhari; Meiman Pratama Harefa; Ammar Zhafran Ryanto (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The Merdeka Curriculum demands a transformation of the learning evaluation system oriented toward the individual needs of students. This study aims to conceptually examine the relationship between formative assessment and the strengthening of differentiated learning within the framework of the Merdeka Curriculum. The method employed is a library research approach using qualitative content analysis and comparative analysis of academic sources published between 2021 and 2025. The findings indicate that formative assessment plays a strategic role as a continuous information-gathering instrument regarding students' learning progress, which subsequently serves as the empirical basis for designing differentiated instruction. The relationship between the two is symbiotic and iterative: formative assessment generates data on learning needs, while differentiated learning provides appropriate instructional responses to that data. The implementation of both in the Merdeka Curriculum still faces several challenges, including limited teacher understanding, high administrative burdens, the diversity of student characteristics, and inadequate facilities and infrastructure. This study affirms that the integration of formative assessment and differentiated learning is key to realizing education that is responsive, equitable, and centered on the development of every individual student.